The Use of Ultra for the Safe Passage of the Anglo-American Expeditionary Forces to North Africa in 1942 - HAROUNI, Brahim (Journal of Human Sciences, 2006)
In his book The Ultra Secret based on his war recollections the former British Intelligence Service Officer, Frederick  W. Winterbotham, revealed that the British cryptanalysts had, during the Second World War, broken the German most secret code used for communications between Berlin and German field commanders. ‘Ultra,’ the information derived from German enciphered messages, was sent out to British field commanders who could, in the light of often detailed information on their enemy’s strategy and tactic, mount their offensive or defensive actions. The British Intelligence Services had, however, remained absolutely silent on this question for about three decades after the war.       The aim of this paper is to try to portray Ultra and the role it played in the mounting of the Anglo-American landings inNorth AfricaonNovember 8, 1942. Three particular points will retain my attention.  First, the historical background through which I will try to shed light on the contribution of the Poles and the French to the breaking of the early signals of the German Enigma machine; second, the British breakthrough; and finally the use of Ultra in the Anglo-American landings in North Africa and why it was kept in the dark for so long.